Strategi Pemasaran Usaha Kopi Cap Teko Di Desa Silungkang Duo, Kecamatan Silungkang, Kota Sawahlunto - Zul Afdal; Aldita Dwi Putri; Nola Try Elsa Gusfantoni; Claudia Cantika Yuri; Muhammad Syauqi Rahman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the marketing strategy implemented by Kopi Cap Teko, a local coffee business in Silungkang Duo Village, Silungkang District, Sawahlunto City, and to identify opportunities for developing more adaptive marketing strategies. This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and documentation, with informants selected using purposive sampling. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the current marketing strategy remains conventional and has not optimally utilized digital media. The main strengths of the business lie in its distinctive product quality and affordable pricing, while its weaknesses are found in limited promotion and distribution. Therefore, it is necessary to develop digital-based marketing strategies and strengthen branding based on local wisdom to enhance product competitiveness. This study contributes to the development of marketing strategies for local micro-enterprises that are adaptive to technological advancements and changing consumer behavior.